Catch Composition of Fix-Liftnet Based-on the Light Color Combination in Pangkep Waters (Torani Journal of Fisheries and Marine Science, 2021)
This study aims to describe the composition of the species and the frequency of occurrence of fix-liftnet based on the combination of white-yellow-blue and white-yellow Light Emitting Diode (LED). The research was carried out in July – October 2020, by following the operation of capturing 1 unit of fix-liftnet with 442 watts of light power each. Data collection includes the type and number of catches based on trips and grouped into main, by-catch and discarded catches. The results showed that the composition of the type of catch consisted of 26 species dominated by common ponyfish, Indonesian oil-sardine, squid, anchovies, crabs, yellow snakehead and fringesscale sardinella. The total catch of the combination of white-yellow-blue lights was 359.8 kg with main catch 74.4%, by-catch 19.8% and waste 5.9%. While the white-yellow color combination is 343.8 kg with 75.8% main catch, 15.5% by-catch and 8.3% waste. Fish species with 100% occurrence frequency were common ponyfish (Leiognathus equulus), flower crab (Portunus pelagicus), squid (Loligo sp), Indonesian oil-sardine (Sardinella gibbosa), and smooth pufferfish (Lagocephalus sceleratus).